Biomphalaria tenagophila potencial vector of schistosoma mansoni in the Paraná River basin (Argentina and Paraguay) - Borda, Carlos Edgardo (2007)
Fil: Borda, Carlos Edgardo. Universidad Nacional del Nordeste. Facultad de Medicina; Argentina.